To add -12/7 and 3/14, we need to find a common denominator. The least common multiple of 7 and 14 is 14.
Next, we convert -12/7 to an equivalent fraction with a denominator of 14 by multiplying the numerator and denominator by 2: -12/7 * 2/2 = -24/14.
Now we can add the fractions:
-24/14 + 3/14 = (-24 + 3)/14 = -21/14.
The sum, -21/14, is already an improper fraction. However, we can further simplify it by dividing both the numerator and denominator by their greatest common divisor (which is 7):
-21/14 รท 7/7 = -3/2.
Therefore, the sum -12/7 + 3/14 is equal to -3/2 as a reduced improper fraction.
Add -12/7 + (3/14) and the sum is a reduced improper fraction
11 answers
Add -1 1/3 + (-4 2/3). (1 point)
To add -1 1/3 and -4 2/3, we first need to convert both mixed numbers to improper fractions.
-1 1/3 can be written as -4/3, because (-3 * 1) + 1 = -3 + 1 = -2, so we have -2/3.
-4 2/3 can be written as -14/3, because (-3 * 4) + 2 = -12 + 2 = -10, so we have -10/3.
Now, we can add the fractions: -4/3 + -14/3 = (-4 - 14)/3 = -18/3.
Lastly, we can simplify the fraction: -18/3 = -6.
Therefore, -1 1/3 + (-4 2/3) equals -6.
-1 1/3 can be written as -4/3, because (-3 * 1) + 1 = -3 + 1 = -2, so we have -2/3.
-4 2/3 can be written as -14/3, because (-3 * 4) + 2 = -12 + 2 = -10, so we have -10/3.
Now, we can add the fractions: -4/3 + -14/3 = (-4 - 14)/3 = -18/3.
Lastly, we can simplify the fraction: -18/3 = -6.
Therefore, -1 1/3 + (-4 2/3) equals -6.
-5.11 + (-1.56)
To add -5.11 and -1.56, we simply add the two numbers together:
-5.11 + (-1.56) = -6.67
Therefore, -5.11 + (-1.56) equals -6.67.
-5.11 + (-1.56) = -6.67
Therefore, -5.11 + (-1.56) equals -6.67.
-1 3/10 + (-4 2/15)
To add -1 3/10 and -4 2/15, we first need to convert both mixed numbers to improper fractions.
-1 3/10 can be written as -13/10, because (-1 * 10) + 3 = -10 + 3 = -7, so we have -7/10.
-4 2/15 can be written as -62/15, because (-15 * 4) + 2 = -60 + 2 = -58, so we have -58/15.
Now, we can add the fractions: -13/10 + -62/15.
To find a common denominator, we note that 10 and 15 have a least common multiple of 30.
Multiplying the numerator and denominator of -13/10 by 3, we get -39/30.
Multiplying the numerator and denominator of -62/15 by 2, we get -124/30.
Now, we can add the fractions:
-39/30 + -124/30 = (-39 - 124)/30 = -163/30.
Therefore, -1 3/10 + (-4 2/15) equals -163/30 as an improper fraction.
-1 3/10 can be written as -13/10, because (-1 * 10) + 3 = -10 + 3 = -7, so we have -7/10.
-4 2/15 can be written as -62/15, because (-15 * 4) + 2 = -60 + 2 = -58, so we have -58/15.
Now, we can add the fractions: -13/10 + -62/15.
To find a common denominator, we note that 10 and 15 have a least common multiple of 30.
Multiplying the numerator and denominator of -13/10 by 3, we get -39/30.
Multiplying the numerator and denominator of -62/15 by 2, we get -124/30.
Now, we can add the fractions:
-39/30 + -124/30 = (-39 - 124)/30 = -163/30.
Therefore, -1 3/10 + (-4 2/15) equals -163/30 as an improper fraction.
-1.2 + 7.6
To add -1.2 and 7.6, we simply add the two numbers together:
-1.2 + 7.6 = 6.4
Therefore, -1.2 + 7.6 equals 6.4.
-1.2 + 7.6 = 6.4
Therefore, -1.2 + 7.6 equals 6.4.
4.6 + (-9.04)
To add 4.6 and -9.04, we simply add the two numbers together:
4.6 + (-9.04) = -4.44
Therefore, 4.6 + (-9.04) equals -4.44.
4.6 + (-9.04) = -4.44
Therefore, 4.6 + (-9.04) equals -4.44.